Decision-making for the infant sleep environment among families with children considered to be at risk of sudden unexpected death in infancy: a systematic review and qualitative metasynthesis. Issue 1 (5th March 2021) - Pease, Anna; Garstang, Joanna J; Ellis, Catherine; Watson, Debbie; Ingram, Jenny; Cabral, Christie; Blair, Peter S; Fleming, Peter J
Abstract : Background: Advice to families to sleep infants on their backs, avoid smoke exposure, reduce excess bedcovering and avoid specific risks associated with cosleeping has greatly reduced sudden unexpected death in infancy (SUDI) rates worldwide. The fall in rates has not been equal across all groups, and this advice has been less effective for more socially deprived families. Understanding decision-making processes of families with infants at risk would support the development of more effective interventions. Aim: To synthesise the qualitative evidence on parental decision-making for the infant sleep environment among families with children considered to be at increased risk of SUDI. Methods: This study was one of three related reviews of the literature for the Child Safeguarding Practice Review Panel's National Review in England into SUDI in families where the children are considered at risk of harm. A systematic search of eight online databases was carried out in December 2019. Metasynthesis was conducted, with themes extracted from each paper, starting with the earliest publication first. Results: The wider review returned 3367 papers, with 16 papers (across 13 studies) specifically referring to parental decision-making. Six overall themes were identified from the synthesis: (1) knowledge as different from action; (2) external advice must be credible; (3) comfort, convenience and disruption to the routine; (4) plausibility and mechanisms of protection; (5) meanings of safety and risk mitigation using alternative strategies; and (6) parents' own expertise, experience and instincts. Conclusion: Interventions that are intended to improve the uptake of safer sleep advice in families with infants at risk of sleep-related SUDI need to be based on credible advice with mechanisms of protection that are understandable, consistent with other sources, widened to all carers of the infant and fit within the complex practice of caring for infants.